2019
DOI: 10.1007/s00253-019-09995-6
|View full text |Cite
|
Sign up to set email alerts
|

Fungal formation of selenium and tellurium nanoparticles

Abstract: The fungi Aureobasidium pullulans , Mortierella humilis , Trichoderma harzianum and Phoma glomerata were used to investigate the formation of selenium- and tellurium-containing nanoparticles during growth on selenium- and tellurium-containing media. Most organisms were able to grow on both selenium- and tellurium-containing media at concentrations of 1 mM resulting in extensive precipitation of elemental selenium and tellurium on fungal surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 81 publications
(126 reference statements)
2
65
0
Order By: Relevance
“…Furthermore, the EDX analysis of the strain TA4 cell detected a presence of zinc elemental composition, indicating the successful biosynthesis of ZnO NPs. Overall, these findings were in an agreement with previous studies on the involvement of cell membrane in the biosynthesis of selenium NPs [59], tellurium NPs [60], and gold NPs [58] by other microorganisms.…”
Section: O-h Stretching and N-h Asymmetric Stretchingsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the EDX analysis of the strain TA4 cell detected a presence of zinc elemental composition, indicating the successful biosynthesis of ZnO NPs. Overall, these findings were in an agreement with previous studies on the involvement of cell membrane in the biosynthesis of selenium NPs [59], tellurium NPs [60], and gold NPs [58] by other microorganisms.…”
Section: O-h Stretching and N-h Asymmetric Stretchingsupporting
confidence: 93%
“…To determine the MTC of LAB strains against Zn 2+ , the agar well diffusion method was carried out according to Hassen et al [68] methods. Zn 2+ solutions were prepared in different concentrations (20,40,60,80,100,200, 300, 400, 500, and 600 mM). Sterile MRS agar plates were prepared and each plate was spread with overnight cultures of LAB strains.…”
Section: Determination Of Zinc-tolerant Lab and Maximum Tolerable Conmentioning
confidence: 99%
“…The CB was suspended in phosphate buffer saline (PBS) and incubated overnight and centrifuged to obtain the suspension containing protein. The extracellular protein of CB suspension and CFS were determined using the Bradford protein assay (Bio-Rad Laboratories Ltd., UK), according to Liang et al 26 . Bovine serum albumin was used as the standard.…”
Section: Production Of Extracellular Proteinmentioning
confidence: 99%
“…Similarly, Moreno-Martin et al 20 reported that the formation of selenium nanoparticles was observed outside the cells of several LAB strains used in their study. It has been reported that the formation of NPs using bacterial biomass is highly dependent on the presence of functional groups on their cell surface 26,28,43 . Hence, the FTIR results obtained in this study substantiated the involvement of several functional groups present on L. plantarum TA4 in the synthesis process of ZnO NPs-CB.…”
Section: Ftir Analysis the Bioactive Molecules Composition Of Cfs Anmentioning
confidence: 99%
“…As a result of heavy cation detoxification using fungal bioreactors, selenium complexes may be reduced to metallic selenium as indicated by the red-orange color of the fungal pellets [ 148 ] or Se NPs as portrayed by field emission transmission electron microscopy (FETEM) images on the fungus cells [ 149 ]. To carry out the biosynthesis of Se NPs and Te NPs, Liang et al [ 150 ] cultured four species of fungus, Aureobasidium pullulans, Mortierella humilis , Trichoderma harzianum and Phoma glomerata , in a suitable medium amended with either 1 mM sodium selenite (Na 2 SeO 3 ) or 1 mM sodium tellurite (Na 2 TeO 3 ), as salt precursors of Se and Te, respectively, while sodium selenate (Na 2 SeO 4 ) was discarded owing to its toxicity. In addition to a diverse response in terms of pH changes and biomass yields, the uptake of the salts by the fungi depends on the species, nature of the salt and contact time.…”
Section: In Vivo Biosynthesis Of Inorganic Nanomaterials Using Funmentioning
confidence: 99%